How Are Residents Trained in Neuropathology? A Survey of Neurology Program Directors in the United States. Issue 11 (17th October 2020) - Rayi, Appaji; Rajneesh, Kiran; Punia, Vineet; Start, Amanda R
Abstract: To understand the current state of neurology residents training in neuropathology, we electronically distributed a 16-item survey to 150 adult and 70 child neurology program directors (PDs). The survey inquired about their program characteristics, neuropathology curriculum and assessment methods, trainee performance, and attitudes. Descriptive analysis was used to summarize categorical variables as frequencies and percentages and continuous as means and standard deviations. We conducted a series of Mann-Whitney U and Fisher's exact tests to evaluate differences between various program characteristics. Sixty-four (29%) PDs responded to the survey, including 45 (30%) adult and 19 (27%) child neurology PDs. Thirty-one programs required a dedicated neuropathology rotation. The majority (92%) used the Residency In-Service Training Examination (RITE) to assess trainee's knowledge. Approximately 86% of the PDs agreed that neuropathology is essential and a defined curriculum is necessary during residency training. There was no difference in the RITE scores between programs. We conclude that a neuropathology rotation was felt to be essential even though the RITE scores did not differ between programs with and without a dedicated rotation. Alternative evaluation and training methods may need consideration. A future survey of all the stakeholders may be required to thoroughly understand and disseminate the neuropathology education well.